Preventive Health Screening of Children and Adolescents - Brazauskienė, Aušra; Stundžienė, Rasa; Semionovienė, Agata (Slauga. Mokslas ir praktika, 2023)
Summary. The purpose of the preventive health check-up of children and adolescents is to assess the harmonious development of patients, identify health disorders, and prevent the occurrence of future diseases. In Lithuania, health checks of children and adolescents are carried out periodically. Family doctors or pediatricians, who suspect health disorders in a child during a preventive health check-up, can prescribe all the necessary instrumental or laboratory tests and send the necessary specialists for consultation. In foreign countries, the culture of preventive health check-ups for children and adolescents is somewhat different, as check-ups are not carried out every year. A literature review was performed using PubMed and Google Scholar search engines, in the MEDLINE electronic database. The search was carried out from 01.11.2022 to 01.02.2023. The systematic review included 16 articles on the topic. After analyzing the scientific articles, it can be stated that preventive health screening of children and adolescents is carried out in many countries, but with the help of different healthcare professionals and also at different time intervals. Preventive examinations in PSP are carried out by a family doctor, a pediatrician, a nurse, an ophthalmologist, a dentist, and in some countries also a physical medicine and rehabilitation doctor and a psychologist.